Civilian Protection in Armed Conflicts: Evolution, Challenges and Implementation - Schütte, Robert (Springer, 2015)
The study analyzes three themes: first, the evolution of the concept of civilians in the course of human history, and secondly, the situation and victimization of civilians in armed conflict since 1990, and third, how the international community since the end of the Cold War to protect civilians has monitored by the mandating robust UN peacekeeping missions. The United Nations Mission in the Congo functions as a case study.